Implementation gap : reference to a policy for persons with disabilities / Ibianaflorinciliana Niane Anthony Aning, Zuraidah Zaaba and Haijon Gunggut - Anthony Aning, Ibianaflorinciliana Niane; Zaaba, Zuraidah; Gunggut, Haijon (Universiti Teknologi MARA, Shah Alam, 2014)
Initially, the one percent policy was mentioned in the Malaysian Civil Service Circular No. 10 of 1988. Subsequently, it was refined and enforced in April 2008. This policy allocated a quota of one percent of the total workforce of every government agency for employing PWDs. However, statistics in October 2013 showed only 1,754 PWDs are employed by government from the approximately 1.4 million civil servants. Moreover, very few government agencies have assigned one percent of their total work force to PWDs. The policy has been in place yet the implementation is far from satisfactory. Hence, by reviewing literature on policy implementation and with reference to the one percent policy for persons with disabilities (PWDs), this paper discussed the possible reasons for the gap between the intended and actual outcome of the policy. Discussion comprised of the interactions of the policy and its institutional setting, relationship of the policy makers and policy implementers and the multiactor character of the policy. The findings demonstrate the complexity of implementing the one percent policy for PWDs.